Evaluating the Student Facilitator and Explain (SFE) Model for Enhancing Critical Thinking in ‘Ilm al-Ma‘ânî at University Level - Zubaidah; Thonthowi, Thonthowi; Akzam, Ismail; Khairani, Riska; Zaitawa, Mukhtar Aminu (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study qualitatively evaluates the use of the Student Facilitator and Explain (SFE) model in enhancing students’ cognitive skills in the ‘Ilm al-Ma’ânî course at the university level. It further explores the correlation between the implementation of the SFE model and student learning outcomes, particularly regarding their comprehension of ‘Ilm al-Ma’ânî concepts, communication skills, and higher-order thinking skills (HOTS), in contrast to traditional instructional approaches. The data were gathered through in-depth interviews, classroom observations, and analysis of relevant academic documents to gain insight into how the SFE model functions and influences the development of students’ thinking abilities. The findings suggest that the model significantly improves students’ critical, analytical, and creative thinking by actively involving them as facilitators and explainers among their peers. In addition, the model promotes interactive learning and deeper cognitive engagement, thereby enhancing the overall quality of classroom instruction. The study concludes by recommending broader implementation of the SFE model in higher education, particularly in courses that traditionally rely on classical methods, to support the growth of students' thinking and independent learning skills.